Memória docente: uma construção a partir de narrativas com relação a educação das artes visuais em escolas rurais - Tasquetto, Angélica D'avila (2009)
This dissertation linked to the Post-Graduate Education, Universidade Federal Line Research Education and Arts has focused thematic reports of memory for visual arts teachers in rural schools in the municipality of Santa Maria / RS. The proposed objectives for the development of this research, concerns brought forward by teachers narratives about their memories as teachers in the rural context and understand how the visual arts teachers work with the visual areas in the educational space. The methodology used in this study is a qualitative approach, data were collected from narrative interviews and field journal as a way to record, then were analyzed by analysis of the interview narrative from the perspective of many-voiced. The subjects were five teachers from rural schools in the municipality of Santa Maria / RS, which granted the interviews in spaces and places predetermined by them. The theoretical, initially structured in authors refer to memory and its constitution (Halbwachs, 2006; Tedesco, 2004; IZQUIERDO 2002). Still on the memory, there have been relations with the trajectories and teaching experiences included authors who provide this thread (ARROYO, 2002; GOODSON 2004 and 2007, Novo, 1999). In a next time, take place problematizaçãoes about rural schools, covering an overview of the conditions of teaching today (PASSADOR, 2006; MOLINA AND JESUS, 2005; ARROYO, 2005; CALDART, 2005). Thus, in discussing the data, we point out the memories of the teachers while teachers in the rural context and all its meanings and creations on the visual sense of space. Thus, this research contributes with regard to the possibility that the recall facts and events may allow the teaching of visual arts.